KOMUNIKASI INTERPERSONAL GURU PEMBIMBING AKADEMIS DENGAN SISWA DALAM MENINGKATKAN PRESTASI DI MAN 1 PEKANBARU - Elga Megri Tamar; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Achievements can be achieved because of the role of a teacher. Students will find it difficult to attain achievement in the absence of a teacher who nurtures, teaches and improves the student's abilities. From the established communication can also be known hobbies and interests and talents of students / I so that even academic tutors can have a solution to channel the student / hobby so as to improve student achievement. This research was conducted to know the interpersonal communication of academic tutors in improving achievement in Madrasah Aliyah Negeri 1 Pekanbaru. The result of the research shows that the interpersonal communication done by the teacher and the students run well. Openness done between teacher and student resulted in the exchange of information so that found learning method according to student character. The empathetic attitude done by the teacher in the form of verbal speech and non verbal action. Supportive attitudes performed between teachers and students include motivating students and praising the results of what they do. Positive behavior is done between teachers and students by always thinking positive when there is a problem with students. The attitude of equality between teachers and students by way of teachers behave as if people who are not too smart so that students do not feel inferior when being in communication with the teacher. Interpersonal communication that is done by academic supervisor teacher give positive impact that is increase of student achievement in MAN 1 Pekanbaru.Keywords: Achievement, Teachers, Students, Schools, Interpersonal Communication